The effect of chamber length and hot air temperature on pulse drying characteristic of aqueous solution [electronic resource] - Eddy Elfiano, 1975-; Fakulti Kejuruteraan Mekanikal (2009)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2009